Exogenous melatonin strengthens saline-alkali stress tolerance in apple rootstock M9-T337 seedlings by initiating a variety of physiological and biochemical pathways - Xian, Xulin; Zhang, Zhongxing; Wang, Shuangcheng; Cheng, Jiao; Gao, Yanlong; Ma, Naiying; Li, Cailong; Wang, Yanxiu (Chemical and biological technologies in agriculture, 2024)
Melatonin (MT) is an important plant growth regulator that significantly regulates the growth and development of plants. Previous studies confirmed the effectiveness of MT in improving plant stress tolerance. In this study, annual M9-T337 seedlings were selected as subjects, and five treatments were applied: control (CK), in which only half the concentration of Hoagland was applied; Saline-alkaline stress treatment (SA, 100 mmol·L −1 saline-alkaline solution); melatonin treatment (MT, CK + 200 μmol L −1 exogenous MT); Saline-alkaline + melatonin treatment (MS, SA + 200 μmol L −1 exogenous MT); and saline-alkaline stress + melatonin + inhibitor treatment (HS, additional 100 μmol L −1 p-CPA treatment to MS). The results showed that saline-alkaline stress negatively affected the growth of M9-T337 seedlings by reducing photosynthetic capacity, increasing Na + , promoting reactive oxygen species such as H 2 O 2 , and changing the osmotic content and antioxidant system. However, the application of exogenous MT effectively alleviated saline-alkaline damage and significantly promoted the growth of M9-T337 seedlings. It significantly increased plant height, diameter, root length, root surface area, volume and activity. Furthermore, MT alleviated osmotic stress by accumulating proline, soluble sugars, soluble proteins and starch. MT improved photosynthetic capacity by delaying chlorophyll degradation and regulating gas exchange parameters as well as fluorescence parameters in leaves. Additionally, MT reduced the Na + /K + ratio to reduce ion toxicity by upregulating the expression of Na + transporter genes ( MhCAX5 , MhCHX15 , MhSOS1 , and MhALT1 ) and downregulating the expression of K + transporter genes ( MhSKOR and MhNHX4 ). In addition, MT can increase antioxidant enzyme activity (superoxide dismutase (SOD), peroxidase(POD), catalase (CAT), ascorbic acid oxidase (AAO), ascorbate peroxidase (APX) and monodehydroascorbate reductase (MDHAR)) in the ASA-GSH cycle and increase ascorbic acid (AsA), reduced glutathione (GSH) and oxidized glutathione (GSSG) levels to counteract the accumulation of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ) and Superoxide anion free radicals (O 2 − ), reducing oxidative damage. Exogenous MT promotes M9-T337 seedlings growth under saline-alkaline stress by responding synergistically with auxin (IAA), gibberellin (GA 3 ) and zeatin (ZT) to saline-alkaline stress. Our results confirm that MT has the potential to alleviate Saline-alkaline stress by promoting root growth, increasing biomass accumulation and photosynthetic capacity, strengthening the antioxidant defense system, maintaining ionic balance, the ascorbate–glutathione cycle and the Osmoregulation facilitates and regulates endogenous hormone levels in M9-T337 seedlings. Graphical Abstract